The Disruptive Power of Online Education: Challenges, Opportunities, Responses - Altmann, Andreas; Ebersberger, Bernd; Mössenlechner, Claudia; Wieser, Desiree (Emerald Publishing Limited, 2018)
This book explores how higher education institutions across the globe respond to the disruptive changes triggered by online technologies. Contributions address transformations regarding program design, business models and pedagogical interventions in a digital teaching environment.